An algorithm for computing wavefront amplitudes and inverse problems (tsunami, electrodynamics, acoustics, and viscoelasticity) - Kabanikhin, S. I.; Krivorotko, O. I. (Doklady. Mathematics, 2016)
An algorithm for computing the amplitude of the leading wavefront generated by an impulse source of oscillations is proposed. According to the algorithm, the fundamental solution is represented in the form of the sum of singular and regular components. As a result, the time required for the amplitude computation is reduced by one order of magnitude. Examples of wavefront amplitudes of tsunami, electromagnetic, acoustic, and viscoelastic waves are given.